How Much Do Means-Tested Benefits Reduce the Demand for Annuities? - Monika Bütler; Kim Peijnenburg; Stefan Staubli (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2013)
We analyze the effect of means-tested benefits on annuitization decisions. Most industrialized countries provide a subsistence level consumption floor in old age, usually in the form of means-tested benefits. The availability of such means-tested payments creates an incentive to cash out (occupational) pension wealth for low and middle income earners, instead of taking the annuity. Agents trade-off the advantages from annuitization, receiving the wealth-enhancing mortality credit, to the disadvantages, giving up free wealth in the form of means-tested supplemental benefits. We find that the availability of means-tested benefits can reduce the desired annuitization levels substantially. Using individual level data, we show that the models predicted annuitization rates as a function of the level of pension wealth are roughly consistent with the cash-out patterns of occupational pension wealth observed in Switzerland.
Keywords: D81; D91; G23; J26; 330; means-tested benefits; occupational pension; annuity; life-cycle model